KELUARGA ERA 4.0: MENILIK PERAN WANITA DI TENGAH ANCAMAN HOAKS - Arif Budiman Budiman; Sri Handayana; Imamul Muttaqin (UIN Raden Mas Said Surakarta, 2021)
Women have a significant role in preventing the spread of hoaxes.The existence of mother figure should be maximized in supporting the hoax prevention mechanism in the family. However, Various data and studies show that women's role in preventing hoaxes appears contradictory. Psychological conditions, emotional factors and stigmatization of woman become barriers for women in obtaining adequate powers to anticipate the transmission of wrong information. As a result, women, especially housewives have strongly pictured as hoax spreaders. The message of the Qur'an contains a conceptual solution in preventing the spread of hoaxes. The internalization of the character of solidarity and a sense of brotherhood is a concept offered by the Qur'an in building communication ethics on social media. Building female characters who can educate and prevent families from spreading hoaxes is needed. It is started with providing education on ethics in communication and media literacy from an early age in schools, families, and the media.